Green Catalysis in API Synthesis: Transitioning from Heavy Metals to Organocatalysts - Juan Martínez; María Rodríguez; Carlos Pérez (Journal of Advanced Pharmaceutical Research Sciences and Sustainability (JAPRSS), 2026)
Background. Green catalysis has become a central concern in pharmaceutical manufacturing due to increasing environmental regulations and sustainability demands. Traditional reliance on heavy metal catalysts in active pharmaceutical ingredient (API) synthesis ensures high efficiency and selectivity but introduces challenges related to toxicity, waste generation, and regulatory compliance. Organocatalysis has emerged as a promising alternative, offering reduced environmental impact and operational simplicity. This study aims to evaluate the feasibility of transitioning from heavy metal catalysis to organocatalysis in API synthesis by comparing their performance, sustainability, and practical applicability. Purpose. A mixed-methods design was employed, integrating experimental benchmarking with comparative analytical evaluation. Representative catalytic systems were selected from literature and replicated under controlled laboratory conditions. Key indicators, including yield, selectivity, reaction time, E-factor, and process mass intensity, were measured and analyzed using inferential statistical techniques. Method. Results indicate that organocatalysis achieves comparable selectivity and acceptable yield performance while significantly reducing environmental impact. Statistical analysis confirms substantial improvements in sustainability metrics, despite moderate increases in reaction time. Case-based evaluation further demonstrates the practical viability of organocatalysis in real-world API synthesis. Results. The findings indicate that, regardless of proficiency level, L1, FLCA, or FLE level, learners prefer more explicit OCF techniques, such as metalinguistics feedback and explicit correction. However, Korean undergraduates scored lower in the majority of OCF strategies (i.e., ignoring, elicitation, recast, explanation, and public feedback) compared to the other participants. Conclusion. Findings suggest that organocatalysis represents a credible and sustainable alternative to heavy metal catalysis. Transitioning toward metal-free catalytic systems can enhance environmental performance without compromising core reaction quality, supporting the advancement of green pharmaceutical manufacturing..